Development and evaluation of an online educational resource about cancer survivorship for cancer nurses: a mixed‐methods sequential study. (10th October 2016) - Shaw, T.; Yates, P.; Moore, B.; Ash, K.; Nolte, L.; Krishnasamy, M.; Nicholson, J.; Rynderman, M.; Avery, J.; Jefford, M.
Abstract: Cancer survivorship is recognised globally as a key issue. In spite of the key role played by nurses in survivorship care, there is an identified gap in nurse's knowledge in this area. This study reports on the development and evaluation of an educational resource for nurses working with people affected by cancer. The resource was designed using adult learning principles and includes a variety of learning materials and point of care resources. A mixed‐methods sequential exploratory design was used to undertake an evaluation of the programme. This included the use of online surveys and semi‐structured interviews with pilot participants. A total of 21 participants completed an online survey and 11 participants completed a telephone interview. Overall, the participants found the Cancer Survivorship resource to be engaging, practical and intuitive. A major theme emerging from the survey and interview data was that the resource was applicable to practice and useful in developing survivorship care plans. Respondents requested additional information be included on the role of various health professionals working in survivorship as well as guidelines on when to make referrals. This study provides evidence that the Cancer Survivorship tool may be a promising vehicle for delivering evidence‐based education on survivorship care.